Chinese clinical practice guidelines for pediatric split liver transplantation - Binsheng Fu; Xiao Feng; Jianrong Liu; Jie Ren; Jin Wang; Shuhong Yi; Yang Yang (Liver Research)
Liver transplantation is an effective treatment for end-stage liver disease in children, and its clinical efficacy has been validated. Split liver transplantation (SLT) can effectively expand the donor liver pool for children. SLT for children has unique clinical characteristics and principles. Establishing technical operation specifications for pediatric SLT plays a significant role in improving clinical efficacy. In this paper, clinical practice guidelines on pediatric SLT were established in the aspect of donor and donor liver evaluation, donor-recipient matching, and ductal segmentation and reconstruction of donor liver, aiming to standardize the technical process, optimize surgical operational details, minimize the risk of complications of SLT for children, further promoting the rapid development of pediatric SLT in China.